Adaptive optics and VLBA imaging observations of recoiling supermassive black hole candidates. Issue 3 (29th September 2022) - Kim, D-C; Kim, Minjin; Yoon, Ilsang; Momjian, E; Kim, Ji Hoon; Letai, J; Evans, A S
ABSTRACT: We present the results of high-resolution adaptive optics imaging observations of four kinematically identified recoiling supermassive black hole (rSMBH) candidates. Ellipse fitting was carried out to measure the spatial offset between the active galactic nucleus (AGN) and the centre of the host galaxy. Two rSMBH candidates (J1713 + 3523 and J2054 + 0049) are found to be offset AGN. However, the Very Long Baseline Array 1.5 GHz continuum imaging observation and spectral decomposition of the [O iii ]5007 line suggest that J1713 + 3523 is a dual AGN and its spatial offset is not due to a recoil event. The spatial offset between the AGN and the centre of the host galaxy in J2054 + 0049 is 0.06 ± 0.01 arcsec (201 ± 22 pc). Spectral decomposition of J2054 + 0049 also suggests that it could be a dual AGN system and the measured spatial offset may not be due to a recoil event.